Proposta de modelo de padronização dos sistemas produtivos da indústria papeleira na criação de conhecimento organizacional - Soares, Ademir de Jesus (2018)
The objective of this research was to propose a standardization model that contributes to the creation of organizational knowledge in the papermaking industry. The research was oriented to answer the problem: - How to create organizational knowledge through the standardization model of the productive system of the papermaking industry? The research site was a papermaking organization located in the southern region of Brazil. Data were collected through the analysis of documents, systems and routines of the unit researched. The research was applied in the main productive unit of the papermaking organization. The study explores the theme of organizational knowledge creation in the context of quality management and continuous improvement, standardization of processes, knowledge transfer and the decomposition of productive processes. In the application of the research was used the technique of observation and direct documentation. For the operationalization of the research the following phases were developed: understanding the applied standardization model, review of the literature on research themes, formulation of a standardization model and application of the model. The result was an understanding of the pattern of standardization practiced, the definition of a hierarchy of standards for the productive unit being researched, the linking of the types of standards with the structure of the processes, the definition of the steps for the standardization cycle, and finally, the evaluation of the relationship between the stages of the proposed model and the modes of knowledge conversion. The results obtained confirm the relationship of all stages of the proposed standardization cycle with the four modes of conversion of the SECI model and that the standardization model proposed in the research can contribute significantly to the creation of organizational knowledge in the researched papermaking industry.